Desempenho produtivo e reprodutivo de um rebanho de vacas F1 Holandês x Gir em Minas Gerais - Lilian dos Santos Ribeiro (2016)
Beef and milk from bovines are among the main animal source foods of Brazilian agribusiness. The tropical climate is a challenge for milk production, therefore the use of crossbred cattle aims to combine resistance factors of zebu with the productive potential of specialized european cattle. The objective of this study was to evaluate the productive and reproductive performances of a herd of F1 Holstein x Gir (HxG) cows raised under appropriate management conditions in Minas Gerais state. The herd during the summer was maneged in a pasture based production system with suplementation of concentrate according to the milk production and in the winter it was fed with sugar cane, citrus pulp and concentrate according to milk production. The characteristics evaluated were: age at first service (IPS), age at first calving (IPP), gestation period (PG), calving to first service interval (IPPS), service period (PS), number of service per pregnancy (SPG), calving interval (IdP), permanence the cows in the herd, total milk production per lactation (PLT), lactation length (DL), average daily milk production (PMD), milk production adjusted to 280 days of lactation (PL280) and to 305 days of lactation (PL305), milk production per calving interval (PLIdP) and lactation curves. The Incomplete Gamma function was used to estimate the parameters of lactation curves. The other characteristics were analyzed using linear mixed models. The herd performs well in all parameters evaluated, with high milk production (6271,56 kg of milk per lactation) compared to national average. The HxG F1 cows are a good alternative to milk production as long as it is guaranteed good conditions of handling and feeding of the herd, and the use of cows derived from breeding programs targeted using genetic improvement criteria.